2018
DOI: 10.1007/s00784-018-2445-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the association of blood-derived growth factors to nanostructured carbonated hydroxyapatite contributes to the maxillary sinus floor elevation? A randomized clinical trial

Abstract: Equivalent new bone formation was observed for cHA in the presence or absence of the BDGF concentrate in bilateral sinus floor elevation after 6 months. Blood-derived growth factors did not improve bone repair when associated with calcium phosphate in sinus lift procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…The researchers in this study followed a checklist of twenty-two items proposed by the Consolidated Standards of Reporting Trials (CONSORT ® ), aimed at complete and transparent reporting of information to reflect on the quality of the study and enable the practice of ideas advocated by evidence-based practice. The minimum sample size (10 individuals per group) was established in an attempt to minimize publication bias [5,25,26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers in this study followed a checklist of twenty-two items proposed by the Consolidated Standards of Reporting Trials (CONSORT ® ), aimed at complete and transparent reporting of information to reflect on the quality of the study and enable the practice of ideas advocated by evidence-based practice. The minimum sample size (10 individuals per group) was established in an attempt to minimize publication bias [5,25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Although previous studies have shown the biocompatibility of CHA in pre-clinical [21] and clinical studies [25], the events of bone repair after dental extraction in humans during intervention with CHA microspheres, remain unclear. Based on this background, the purpose of the present study was to compare the effects of bioabsorbable nanostructured carbonated hydroxyapatite (CHA) with a bovine xenograft (Bio-Oss ® ), known to be biocompatible and osteoconductive, and clot (control group) in alveolar preservation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used carbonated hydroxyapatite synthesized at 37 °C, the same temperature used in a previous study [ 4 , 5 , 32 ]. Patel et al showed that HA synthesized by lower temperature exhibited a more considerable inflammatory cell and fibroblastic proliferation, with a higher concentration of Ca 2+ in the ECM, and a difference between them in physical parameters: porosity and crystal morphology [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite (HA) is a naturally occurring mineral, a component of bone and teeth, and a synthesized material with wide application in medicine for the healing of bones. Due to its biocompatibility and bioactivity [ 1 , 2 , 3 ] HA has been used in dentistry as a bone substitute for alveolar ridge preservation [ 4 ], sinus lift elevation [ 5 ], and as a drug carrier to prevent and control inflammatory processes, chronic infections, and to enhance the endogenous healing capacity of bone defects, which ultimately result in the significant improvement of bone regeneration [ 6 , 7 , 8 , 9 ]. Although, the main limitation of HA ceramics is their high crystallinity, low adsorption capacity for drugs, and poor in vivo bioabsorbability.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium phosphate has been widely used as a bone substitute; 7,8 dental-implant coating; 9 and carrier for proteins, 10 growth factors, 11 and drugs [12][13][14] due to its similarity to bone tissue's mineral content and suitable cellattachment capacity. Among the calcium phosphates, hydroxyapatite in particular has been favored given its biocompatibility, safety, predictability, unlimited availability, lower morbidity for the patient, and cost-effectiveness, which offer significant advantages and make it a good choice for dental-implant coatings.…”
Section: Introductionmentioning
confidence: 99%